Evaluation of non‐invasive prenatal testing to detect chromosomal aberrations in a Chinese cohort. Issue 11 (27th August 2019) - Cui, Wanting; Liu, Xiaoliang; Zhang, Yuanyuan; Wang, Yueping; Chu, Guoming; He, Rong; Zhao, Yanyan
Abstract: The aim of this study was to evaluate the clinical feasibility of non‐invasive prenatal testing (NIPT) to detect foetal copy number variations (CNVs). Next‐generation sequencing for detecting foetal copy number variations (CNVs) was performed on the collected samples from 161 pregnancies with ultrasound anomalies and negative NIPT results for aneuploidy. The performance of NIPT for detecting chromosome aberrations was calculated. The sensitivity and specificity of NIPT for detecting CNVs > 1 Mb were 83.33% and 99.34%; the PPV and negative predictive rate (NPV) were 90.91% and 98.68%. Non‐invasive prenatal testing can be performed to detect chromosomal aberrations in first trimester with high performance for CNVs, and occasional discordant cases are unavoidable.